Women's Participation in Mediation Houses in Banjarmasin City - Zulaeha, Mulyani; Faishal, Achmad; Anwary, Ichsan; Suprapto, Suprapto; Saprudin, Saprudin; Tornado, Anang Shophan; Ilmy, Muhammad Azianoor; Mustika, Cindyva Thalia (Universitas Syiah Kuala, 2025)
Community service in the Compulsory Lecturer Service Program (PDWA) aims to develop the capacity of women in resolving disputes/conflicts and the strategic role of women's involvement in the Mediation House, so that equality of position is created between men and women to obtain opportunities/opportunities and participation in development, especially in facilitating the resolution of disputes and disputes in the community through mediation channels that prioritize deliberation and consensus with an approach that prioritizes peace. Through this service theme, it is hoped that it can inspire women to take a role in the Mediation House. The results of this service activity show that women also have the capacity and ability to become facilitators in resolving disputes in the community through mediation, because in principle women have good communication skills to facilitate the resolution of disputes/conflicts between the parties. Thus, women's participation in the mediation space can be an important investment for a better future in Banjarmasin City, which has a domino effect on increasing women's legal literacy and strengthening social networks (agents of change).